A cementing toughened weak retarding fluid loss agent and a preparation method thereof

By preparing a toughening, weakly retarding, and water-loss-reducing agent, and combining nanomaterials and polymer materials, the problem of water loss in cement slurry under high temperature and high pressure conditions was solved, achieving stability in water loss reduction and thickening performance under extreme conditions, making it suitable for high temperature and high pressure cementing operations.

CN117603398BActive Publication Date: 2026-11-06SOUTHWEST PETROLEUM UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311574448.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-23
Publication Date
2026-11-06
Estimated Expiration
2043-11-23

AI Technical Summary

Technical Problem

Existing fluid loss reducing agents are unstable under high temperature and high pressure conditions, leading to increased water loss in cement slurry, which affects cementing quality and safety. Furthermore, the viscosity of single synthetic materials decreases at high temperatures, making it impossible to effectively maintain the thickening performance and strength of cement slurry.

Method used

The toughening, weakly slowing, and dehydration-reducing agent is composed of adsorbent monomers, temperature-sensitive monomers, temperature-resistant rigid monomers, and modified nanocomposites. It is prepared by copolymerization, introducing nanomaterials to block capillary pores and form a hybrid cross-linked network structure, thereby improving temperature resistance and viscosity stability.

Benefits of technology

It effectively reduces the water loss of cement slurry under high temperature and high pressure conditions, maintains the thickening performance and strength of cement slurry, and improves the temperature resistance and dynamic viscosity of the water loss reducing agent, making it suitable for cementing operations under high temperature and high pressure environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117603398B_ABST
    Figure CN117603398B_ABST
Patent Text Reader

Abstract

This invention discloses a toughening, weakly retarding, and fluid loss reducing agent for cementing and its preparation method. The fluid loss reducing agent is prepared from the following components in the indicated mass percentages: 20-35% adsorbent monomer, 10-15% thermosensitive monomer, 5-10% heat-resistant rigid monomer, 0.5-1.5% modified nanocomposite material, 0.1-0.5% initiator, and 45-60% water. The modified nanocomposite material is selected from any one or more of the following: silane coupling agent-modified carboxyl carbon nanotubes with silica-grafted surfaces, hydroxyl carbon nanotubes, and graphene oxide. The fluid loss reducing agent of this invention can effectively reduce the fluid loss of cement slurry systems. It exhibits good high-temperature resistance and excellent fluid loss reducing performance, and has no adverse effects on the thickening properties and strength development of cement slurry systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a fluid loss reducing agent, specifically to a toughening, weakly slow-setting fluid loss reducing agent for cementing and its preparation method. Background Technology

[0002] With the increasing demand for oil and gas resources, oil and gas exploration is gradually developing from shallow wells to deep and ultra-deep wells, which brings with it extreme formation environments such as high temperature and high pressure. During cementing, cement slurry loses water as pressure increases upon injection into the formation. This water loss leads to a decrease in the rheological properties of the cement slurry, and the intrusion of liquid phase into the formation can cause reservoir damage. Therefore, reducing cement slurry water loss is of great significance. As one of the main admixtures in oil well cementing engineering, water loss reducing agents mainly play a role in reducing cement slurry water loss, ensuring cement slurry performance, improving cementing quality, and preventing contamination of oil and gas production layers due to water loss.

[0003] Currently, the mechanism of action of water loss reducing agents in cement paste is believed to mainly include the following aspects:

[0004] (1) By adsorbing cement particles by polar groups in the polymer monomer and by reducing the viscosity of the water loss agent itself, the viscosity of the cement slurry is increased, thereby reducing the flowability of free water and playing the role of reducing water loss in the cement slurry.

[0005] (2) By adding granular materials to the cement slurry, the water loss channels of the cement filter cake are blocked by the principle of particle gradation, thereby achieving the purpose of reducing water loss in the cement slurry.

[0006] (3) By introducing ionic monomers to adsorb ions on the surface of cement particles in cement slurry, an adsorption hydration layer is formed, reducing the chance of loss of free water in cement slurry.

[0007] Research on the synthesis of water loss control agents, both domestically and internationally, has transitioned from initial research on natural materials to synthetic materials. Their excellent water solubility and adsorption properties can effectively improve the water loss control performance of water loss control agents in cement pastes. However, this also brings a series of problems, as follows:

[0008] (1) The way of action of simple synthetic material water loss reducing agents in cement slurry is relatively simple. They can only exert the effect of reducing water loss through chemical adsorption in cement slurry, which can easily lead to the failure of water loss reducing agent performance under high temperature and high pressure environment.

[0009] (2) Due to chemical adsorption, the water loss reducing agent reduces the contact between cement particles and free water, thereby prolonging the thickening time of cement slurry and causing problems such as poor thickening performance of cement slurry and impact on cementing safety.

[0010] (3) At present, although the initial viscosity of single synthetic polymer water loss reducing agents is relatively large, the viscosity decreases sharply with the increase of ambient temperature, which is not conducive to the development of the dynamic viscosity of cement paste at high temperature. Summary of the Invention

[0011] The purpose of this invention is to provide a toughening, weakly retarding, and fluid loss reducing agent for cementing and its preparation method. This agent can effectively reduce the fluid loss of cement slurry systems. It has good high-temperature resistance and excellent fluid loss reduction performance, and has no side effects on the thickening performance and strength development of cement slurry systems.

[0012] To achieve the above objectives, the present invention provides a cementing toughening and weakly retarding fluid loss reducing agent, which is prepared from the following components in the indicated mass percentages: 20-35% adsorbent monomer, 10-15% thermosensitive monomer, 5-10% temperature-resistant rigid monomer, 0.5-1.5% modified nanocomposite material, 0.1-0.5% initiator, and 45-60% water; wherein the modified nanocomposite material is selected from any one or more of the following: silane coupling agent modified carboxyl carbon nanotubes with silica-grafted surface, hydroxyl carbon nanotubes, and graphene oxide.

[0013] Preferably, the adsorbent monomer is selected from any one or more of sodium 2-acrylamide-2-methylpropanesulfonate (AMPS), acrylamide (AM), itaconic acid (IA), and maleic acid (MA).

[0014] Preferably, the adsorbent monomer is selected from any one of the following: a combination of sodium 2-acrylamide-2-methylpropanesulfonate and acrylamide, a combination of sodium 2-acrylamide-2-methylpropanesulfonate and itaconic acid, a combination of sodium 2-acrylamide-2-methylpropanesulfonate and maleic acid, or a combination of acrylamide and maleic acid.

[0015] Preferably, the temperature-sensitive monomer is selected from any one or more of N,N-diethylacrylamide (DEAA), N-isopropylacrylamide (NIPAM), and N,N-dimethylacrylamide (DMAA).

[0016] Preferably, the heat-resistant rigid monomer is selected from any one or more of maleic anhydride (MAH), sodium styrene sulfonate (SSS), and N-vinylpyrrolidone (NVP).

[0017] Preferably, the initiator is selected from ammonium persulfate (APS) and / or potassium persulfate (KPS).

[0018] Preferably, the silane coupling agent is selected from KH-570.

[0019] Another objective of this invention is to provide a method for preparing the aforementioned cementing toughening, weakly retarding, and fluid loss reducing agent. The method comprises: dissolving an adsorbent monomer, a temperature-sensitive monomer, a temperature-resistant rigid monomer, and a modified nanocomposite material in water; heating and stirring until the sample is completely dissolved, obtaining a mixed solution as the initial reaction solution; heating the initial reaction solution to 70–80°C under an inert gas atmosphere to obtain an intermediate reaction solution; dissolving an initiator in water to obtain an initiator solution; uniformly adding the initiator solution dropwise into the intermediate reaction solution, stirring and mixing, and reacting at a constant temperature of 70–80°C for 3–5 hours to obtain a liquid polymerization product; dialyzing the liquid polymerization product in a dialysis bag, freeze-drying, and grinding to obtain the toughening, weakly retarding, and fluid loss reducing agent.

[0020] Preferably, the initiator solution is uniformly added dropwise to the intermediate reaction solution within 1 to 2 hours and stirred at a speed of 200 r / min.

[0021] Preferably, the liquid polymer product is dialyzed in a dialysis bag with a molecular weight cutoff of 3500 Da, the remaining liquid after dialyzing is frozen at -20°C, then freeze-dried, and finally the solid particles obtained by freeze-drying are ground.

[0022] More preferably, the liquid polymer product is dialyzed in a dialysis bag with a molecular weight cutoff of 3500 Da for 7 days, with the water changed every 12 hours. The remaining liquid after dialyzing is then frozen at -20°C for 1 day, and then dried in a freeze dryer for 2 days. Finally, the freeze-dried solid particles are ground in a mortar and pestle.

[0023] Preferably, the preparation method of the modified nanocomposite material includes: dissolving one or more of carboxyl carbon nanotubes, hydroxyl carbon nanotubes, and graphene oxide in an alcohol solvent, adding a surfactant, and ultrasonically dispersing at 40°C to obtain dispersion one; adding ammonia / ammonium chloride buffer solution dropwise to dispersion one, adjusting the pH of the mixed solution to 8-10, and continuing ultrasonic dispersion at a constant temperature of 40°C after the buffer solution is added to obtain dispersion two; adding tetraethyl orthosilicate to dispersion two, and ultrasonically dispersing at a constant temperature of 40°C to obtain dispersion two. Silicon was uniformly grafted onto the surface of carbon nanotubes via Si-OC bonds. The reaction solution was rinsed and vacuum filtered to obtain a pure primary nanocomposite material. A 90% ethanol solution was prepared, and the pH of the ethanol solution was adjusted to 5 with hydrochloric acid. The ethanol solution and a silane coupling agent were stirred at a constant temperature of 65°C to allow the silane coupling agent to be fully hydrolyzed in the ethanol solution. The pure primary nanocomposite material was added to the hydrolyzed solution of the silane coupling agent, and the reaction was stirred at 70°C. After the reaction was completed, the reaction solution was dehydrated and dried at 80°C to finally obtain the modified nanocomposite material.

[0024] Preferably, the mass ratio of the alcohol solvent to any one or more of carboxyl carbon nanotubes, hydroxyl carbon nanotubes, and graphene oxide is 10:1.

[0025] Preferably, the alcohol solvent is ethanol.

[0026] Preferably, the mass ratio of the ammonia / ammonium chloride buffer solution to any one or more of carboxyl carbon nanotubes, hydroxyl carbon nanotubes, and graphene oxide is 1:2.

[0027] Preferably, the ammonia / ammonium chloride buffer solution is added dropwise to the dispersion solution within 30 minutes.

[0028] Preferably, after the buffer solution is added, continue to sonicate at a constant temperature for 1 hour.

[0029] Preferably, the mass ratio of the tetraethyl orthosilicate to any one or more of the carboxyl carbon nanotubes, hydroxyl carbon nanotubes, and graphene oxide is 3:10.

[0030] Preferably, tetraethyl orthosilicate is added to the second dispersion within 10 minutes, and the mixture is ultrasonically dispersed at a constant temperature of 40°C at a rotation speed of 500 r / min for 5 hours.

[0031] Preferably, the mass ratio of the 90% ethanol solution to the silane coupling agent is 100:1.

[0032] Preferably, the ethanol solution and silane coupling agent are stirred at a constant temperature of 65°C at 400 r / min for 4 h.

[0033] Preferably, the mass ratio of the silane coupling agent to the pure primary nanocomposite material is 1:10.

[0034] Preferably, the pure primary nanocomposite material is added to the hydrolysis solution of the silane coupling agent, and the mixture is stirred at 400 r / min for 6 h at 70 °C.

[0035] Preferably, the reaction solution is dehydrated and dried at 80°C for 24 hours.

[0036] The cementing toughening, weakly retarding, and fluid loss reducing agent and its preparation method of the present invention have the following advantages:

[0037] (1) This invention introduces modified nanocomposite materials, with nanomaterials as the dispersed phase and polymer materials as the continuous phase, combining the rigidity of nanomaterials with the toughness and processability of synthetic polymer materials; the introduction of modified rigid monomers and temperature-sensitive monomers can not only improve the temperature resistance of the fluid loss reducing agent, but also reduce the initial viscosity of the fluid loss reducing agent, and help improve the dynamic viscosity of the fluid loss reducing agent under high temperature conditions; the introduced materials solve the main problems of existing fluid loss reducing agents. In practical applications, the temperature resistance limit of the fluid loss reducing agent can reach 220℃. It has good stability under high temperature and high pressure conditions and can effectively maintain the fluid loss reduction performance of the cement slurry system under extreme conditions, while having no side effects on the thickening performance and strength development of the cement slurry;

[0038] (2) This invention adds three nanomaterials, namely graphene oxide, carboxylated carbon nanotubes or hydroxyl carbon nanotubes, to the water loss reducing agent. In cement slurry, these materials can seal capillary pores and micro-cracks. The high bond energy between carbon atoms can improve the strength, fracture toughness and wear resistance of cement. Nano-silica is generated on the surface of carbon materials. Nano-silica mainly plays a nucleation role in the early stage. Through its strong "volcanic ash effect", it promotes the formation of calcium hydroxide CH hydrate calcium silicate CSH in cement slurry, thereby weakening the retarding performance of the water loss reducing agent. The size effect of particulate materials improves the pore structure and reduces the porosity. From the perspective of pore size distribution, it improves the quality of cement filter cake, improves the comprehensive performance of the water loss reducing agent, and maintains the excellent water loss reducing performance of cement slurry under high temperature and high pressure conditions.

[0039] (3) This invention introduces a rigid monomer, which can improve the temperature resistance and initial viscosity of the polymerization product through the unique rigid structure of the monomer, making it convenient for industrial mass production. The strong polar rigid ring structure of the monomer can effectively enhance the rotational energy of the polymer bond under high temperature reaction conditions, thereby improving the chain extension of the dehydration agent product and reducing the viscosity of the finished polymerization product;

[0040] (4) The thermosensitive monomer introduced in this invention gives the water loss reducing agent a thermosensitive effect, improving its temperature resistance in cement slurry. The thermosensitive effect weakens the water solubility of the hydrophobic groups in the water loss reducing agent at high temperatures, causing them to aggregate and form associated hydrophobic microdomains. Through KH-570 graft modification on the silica surface, a hybrid cross-linked network structure is formed, which strengthens the binding force of the water loss reducing agent on free water, promotes the formation of a reversible physical network structure, improves the polymer's hydrodynamic volume and viscosity stability at high temperatures, and improves the temperature resistance of the water loss reducing agent in the cement slurry system.

[0041] (5) The water loss reducing agent of the present invention is synthesized by aqueous solution copolymerization, so the overall operation process is simple, the raw materials are easy to obtain, the polymer yield is high, and the viscosity of the polymer product is lower than that of most existing water loss reducing agents, making it easier to achieve industrial-scale mass production of water loss reducing agents. The toughening and weakly retarding water loss reducing agent prepared by this method can effectively reduce the water loss of cement slurry system. The water loss reducing agent has good high temperature resistance and excellent water loss reducing performance, and has no side effects on the thickening performance and strength development of cement slurry system. Attached Figure Description

[0042] Figure 1 The results of the cement slurry thickening experiment in Experiment Example 1 of this invention are shown.

[0043] Figure 2 The results show the dynamic viscosity of the cement slurry in Experiment Example 2 of this invention.

[0044] Figure 3 The images shown are electron micrographs of cement filter cakes from Experiment 4 of this invention; (a) Comparative Example 1; (b) Example 2.

[0045] Figure 4 This is the pore distribution curve of the cement filter cake in Experimental Example 4 of the present invention. Detailed Implementation

[0046] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0047] Example 1

[0048] A cementing agent for toughening, slowing, and reducing water loss is prepared from the following components by mass percentage: 20% adsorbent monomer (15% AMPS + 5% AM), 15% temperature-sensitive monomer (DEAA), 7% temperature-resistant rigid monomer (MAH), 0.75% modified nanocomposite material (CCNTs-NS), 0.25% initiator (APS), and 57% ultrapure water.

[0049] The modified nanocomposite material CCNTs-NS described above was prepared by the following method:

[0050] (1) Dissolve 10 parts of carboxylated carbon nanotubes (CCNTs) in 100 parts of ethanol, add 3 parts of surfactant cetyltrimethylammonium CTAB, and ultrasonically disperse at 40°C for 30 min.

[0051] (2) Slowly add 5 parts of ammonia / ammonium chloride buffer (pH=8-10) to the above dispersion, and control the buffer to be added to the dispersion in 30 minutes. Adjust the pH of the mixed solution to 8-9. After the buffer is added, continue to sonicate at 40℃ for 1 hour to make the solution evenly dispersed.

[0052] (3) After the solution in step (2) is evenly dispersed, add 3 parts of tetraethyl orthosilicate (TEOS) liquid within 10 min and ultrasonically disperse at a constant temperature of 40°C for 5 h at a speed of 500 r / min. In the dispersion, silica is uniformly grafted onto the surface of carbon nanotubes through Si-OC bonds.

[0053] (4) The reaction solution was rinsed with ethanol and then vacuum filtered to obtain a pure primary nanocomposite material.

[0054] (5) Prepare 100 parts of 90% ethanol solution and adjust the pH of the ethanol solution to 5 with hydrochloric acid. Dissolve the ethanol solution and 1 part of silane coupling agent KH-570 in a beaker and stir at 400 r / min for 4 h at a constant temperature of 65℃ to allow KH-570 to be fully hydrolyzed in the ethanol solution.

[0055] (6) After stirring, add 10 parts of pure primary nanocomposite material and stir at 400 r / min for 6 h at 70 °C. Finally, use a forced-air drying oven to dehydrate and dry the reaction solution at 80 °C for 24 h to obtain CCNTs-NS modified nanocomposite material.

[0056] The preparation method of the above-mentioned cementing toughening, weakly retarding, and fluid loss reducing agent includes the following steps:

[0057] (1) Strongly adsorbent monomers AMPS (15%) and AM (5%), as well as thermosensitive monomer DEAA (15%), heat-resistant rigid monomer MAH (7%) and modified nanocomposite CCNTs-NS (0.75%) were placed in ultrapure water (40%), heated and stirred until the sample was completely dissolved, and then poured into the reaction vessel. The resulting mixed solution was the initial reaction solution.

[0058] (2) Next, nitrogen gas is introduced into the reactor for 30 minutes, and the initial reaction solution obtained in step (1) is heated to 80°C to obtain the intermediate reaction solution.

[0059] (3) The initiator APS (0.25%) was mixed in ultrapure water (17%) to obtain an initiator solution;

[0060] (4) Next, the initiator solution obtained in step (3) is uniformly dripped into the reactor within 1 hour, and it is stirred and mixed with the intermediate reaction liquid obtained in step (2). The stirring speed is controlled at 200 r / min, and the reaction is carried out at 80°C for 3 hours to obtain the liquid polymerization product.

[0061] (5) The liquid polymerization product obtained in step (4) is dialyzed in a dialysis bag with a molecular weight cutoff of 3500 Da for 7 days, with the water changed every 12 hours. The remaining liquid after dialyzing is then frozen at -20°C for 1 day, and then dried in a freeze dryer for 2 days. Finally, the solid particles obtained from freeze drying are ground in a mortar and pestle. This purification step eliminates the influence of monomers that did not participate in the polymerization, thus obtaining the toughening, weak retardation, and water loss reduction agent solid powder.

[0062] Example 2

[0063] A cementing agent for toughening, slowing, and reducing water loss is prepared from the following components by mass percentage: 21% adsorbent monomer (16% AMPS + 5% IA), 12.5% ​​temperature-sensitive monomer (NIPAM), 5% temperature-resistant rigid monomer (SSS), 1% modified nanocomposite material (HCNTs-NS), 0.5% initiator (KPS), and 60% ultrapure water.

[0064] The preparation method of the above-mentioned modified nanocomposite material HCNTs-NS is basically the same as the preparation method of the modified nanocomposite material CCNTs-NS in Example 1, except that hydroxyl carbon nanotubes HCNTs are used instead of carboxyl carbon nanotubes CCNTs.

[0065] The preparation method of the above-mentioned cementing toughening weak retarder setting fluid reduction agent is basically the same as the preparation method of the cementing toughening weak retarder setting fluid reduction agent in Example 1, the difference being:

[0066] In step (1), the strongly adsorbent monomers AMPS (16%) and IA (5%), as well as the thermosensitive monomer NIPAM (12.5%), the temperature-resistant rigid monomer SSS (5%), and the modified nanocomposite HCNTs-NS (1%) are placed in ultrapure water (50%).

[0067] In step (2), the temperature is raised to 75°C;

[0068] In step (3), the initiator KPS (0.5%) is miscible in ultrapure water (10%);

[0069] In step (4), the initiator solution is uniformly added dropwise into the reactor over 2 hours; and the reaction is carried out at a constant temperature of 75°C for 4 hours.

[0070] Example 3

[0071] A cementing agent for toughening, slowing, and reducing water loss is prepared from the following components by mass percentage: 33% adsorbent monomer (25% AM + 8% MA), 10% temperature-sensitive monomer (DMAA), 10% temperature-resistant rigid monomer (NVP), 1.5% modified nanocomposite material (GO-NS), 0.5% initiator (KPS), and 45% ultrapure water.

[0072] The preparation method of the modified nanocomposite material GO-NS is basically the same as that of the modified nanocomposite material CCNTs-NS in Example 1, except that graphene oxide GO is used instead of carboxyl carbon nanotubes CCNTs.

[0073] The preparation method of the above-mentioned cementing toughening weak retarder setting fluid reduction agent is basically the same as the preparation method of the cementing toughening weak retarder setting fluid reduction agent in Example 1, the difference being:

[0074] In step (1), the strongly adsorbent monomers AM (25%) and MA (8%), as well as the thermosensitive monomer DMAA (10%), the temperature-resistant rigid monomer NVP (10%), and the modified nanocomposite GO-NS (1.5%) are placed in ultrapure water (40%).

[0075] In step (2), the temperature is raised to 70°C;

[0076] In step (3), the initiator KPS (0.5%) is miscible in ultrapure water (5%);

[0077] In step (4), the initiator solution is uniformly added dropwise into the reactor over 1.5 hours; and the reaction is carried out at a constant temperature of 70°C for 5 hours.

[0078] Example 4

[0079] A cementing agent for toughening, slowing, and reducing water loss is prepared from the following components by mass percentage: 35% adsorbent monomer (20% AMPS + 15% MA), 11.4% temperature-sensitive monomer (NIPAM), 5% temperature-resistant rigid monomer (SSS), 0.5% modified nanocomposite material (CCNTs-NS), 0.1% initiator (APS), and 48% ultrapure water.

[0080] The preparation method of the above-mentioned cementing toughening weak retarder setting fluid reduction agent is basically the same as the preparation method of the cementing toughening weak retarder setting fluid reduction agent in Example 1, the difference being:

[0081] In step (1), the strongly adsorbent monomers AMPS (20%) and MA (15%), as well as the thermosensitive monomer NIPAM (11.4%), the temperature-resistant rigid monomer SSS (5%), and the modified nanocomposite CCNTs-NS (0.5%) are placed in ultrapure water (33%).

[0082] In step (2), the temperature is raised to 75°C;

[0083] In step (3), the initiator APS (0.1%) is miscible in ultrapure water (15%);

[0084] In step (4), the initiator solution is uniformly added dropwise into the reaction vessel over 2 hours; and the reaction is carried out at a constant temperature of 75°C for 4 hours.

[0085] Comparative Example 1

[0086] A linear copolymer high-temperature fluid loss reducing agent for cementing is prepared in a manner that is basically the same as the toughening and weakly retarding fluid loss reducing agent for cementing in Example 1, except that:

[0087] In step (1), the strongly adsorbent monomers AMPS (20%) and IA (13%), as well as the thermosensitive monomer DEAA (10%) and the temperature-resistant rigid monomer SSS (7.5%), are placed in ultrapure water (33%).

[0088] In step (2), the temperature is raised to 70°C;

[0089] In step (3), the initiator APS (0.5%) is miscible in ultrapure water (9%);

[0090] In step (4), the reaction is carried out at a constant temperature of 75°C for 4 hours.

[0091] Experiment Example 1: Performance Test of Cementing Fluid Loss Control Agent

[0092] The performance of the cementing fluid loss reducing agents prepared using Examples 1-4 and Comparative Example 1 was tested to explore the overall compatibility of the examples with other admixtures. The cement slurry formula was: 100% Jiahua G-grade cement + 35% quartz sand + 3% retarder + 6% fluid loss reducing agent + 1.2% suspending agent + water (W / C = 0.44; ρ = 1.90 g / cm³). 3 The retarder used was GH-9 produced by Weihui Chemical Co., Ltd. in Henan Province, and the suspending agent was prepared according to "Preparation and performance characterization of suspending agent for cementing at 200℃" ([J]. Drilling Fluid and Completion Fluid, 2022, Vol. 39 (4): 472-480). Cement slurry with a water-cement ratio of 0.44 was prepared according to GB / T19139—2012 "Test Methods for Oil Well Cement". The performance of the cement slurry was evaluated according to GB / T19139—2012 "Test Methods for Oil Well Cement", including the water loss reduction, compressive strength, fluidity, settling stability and setting regulation of the cement slurry.

[0093] Table 1. Comprehensive performance test results of cement grout

[0094]

[0095] The test results in Table 1 show that the cementing fluid loss reducers in Examples 1-4 and Comparative Example 1 exhibit good overall compatibility with other admixtures. The toughening and weakly retarding fluid loss reducers in Examples 1-4 perform well, controlling API water loss in the cement slurry to less than 50 mL at 220℃. The compressive and tensile strengths of the cement stone after 48 hours of curing are excellent, and the fluidity of the cement slurry at 25℃ and 90℃ fully meets the cementing requirements, although the fluidity at 25℃ is generally lower than at 90℃. In contrast, the linear copolymer fluid loss reducer in Comparative Example 1 only barely exerts its fluid loss reduction effect at temperatures below 180℃. The compressive and tensile strengths of the cement stone after 48 hours of curing, as well as the fluidity of the cement slurry at different temperatures, barely meet the cementing requirements, and the fluidity of the cement slurry at 25℃ is higher than at 90℃.

[0096] The significant performance differences between Examples 1-4 and Comparative Example 1 are due to the following two reasons:

[0097] (1) Under high temperature conditions, the hybrid composite water loss reducing agent can play a temperature-sensitive hydrophobic association role in cement slurry, weakening the trend of the overall consistency of cement slurry decreasing with increasing temperature, thus providing excellent water loss reducing properties for cement slurry under high temperature conditions.

[0098] (2) CCNTs, HCNTs and GO were introduced into the hybrid composite water loss reducing agent, which combined the excellent physical properties of nanomaterials with the chemical properties of linear copolymers, thereby accelerating the development of the compressive and tensile strength of cement stone and enabling the water loss reducing agent to play a toughening role for cement stone.

[0099] Thickening effect in Experiment Example 2

[0100] High-temperature and high-pressure thickening experiments were conducted on the cement slurries (same as the cement slurry in Experiment 1) prepared with the water loss reducing agent of Examples 1-4 (i.e., Examples 1-4) and Comparative Example 1. According to API standards, the specific operations are as follows:

[0101] (1) Place the slurry cup filled with cement slurry on the drive plate inside the high pressure vessel, and start rotating the slurry cup. Insert the potentiometer and make it engage with the drive plate on the stirring blade shaft. Start injecting hydrocarbon oil into the high pressure vessel. At this time, the stirring blade shaft should not rotate.

[0102] (2) Tighten the top cover assembly of the autoclave, insert the temperature sensor through the center hole on the top cover, and screw the screw on it in partially. After the autoclave is filled with hydrocarbon oil, tighten the screw on the temperature sensor. The test should begin within 5 min ± 15 s after the cement slurry mixing is completed;

[0103] (3) During the test, the cement slurry in the slurry cup should be heated and pressurized according to the corresponding test plan. The test plan can be calculated or taken from the plan table. The temperature of the cement slurry is measured by a thermocouple located at the center of the slurry cup. The tip of the thermocouple should be in a vertical position, inserted into the stirring shaft in the slurry cup, between 4.45cm and 8.89cm from the base of the slurry cup. Since different models of thickeners have different sizes, thermocouples should be used with care to ensure that the thermocouple used is compatible with the thickener and that the tip of the thermocouple is in the correct position as described above.

[0104] (4) The thickening time is the time elapsed from the start of heating and pressurizing until the consistency reaches 100 Bc. The consistency of the cement paste at the end of the thickening time test should be recorded.

[0105] Among them, cement slurry without added water loss reducing agent was used as the blank group.

[0106] like Figure 1 The figures show the thickening data of cement slurry in Examples 1-4 and Comparative Example 1 at 150℃ and 94.4MPa. The comparison results show that the cementing toughening and weakly retarding fluid-reducing agents used in Examples 1-4 have a positive effect on the thickening performance of cement slurry, which can extend the thickening time of cement slurry in the short term (<60min) and will not cause abnormal phenomena such as "core formation", "bulging", or "stepping" in cement slurry. However, although the linear copolymer fluid-reducing agent in Comparative Example 1 does not cause abnormal phenomena in cement slurry, it will strongly prolong the thickening time of cement slurry. At the same dosage, the thickening time is extended by 259min at 150℃, which is not conducive to the development of cement stone strength and construction safety.

[0107] Experimental Example 3 Dynamic Viscosity

[0108] The dynamic viscosity of the water loss reducing agents of Examples 1-4 and Comparative Example 1 under different temperature conditions was tested using a rotational viscometer. The data are as follows: Figure 2 As shown, the viscosity of the cementing toughening and weakly retarded fluid loss reducing agent in Examples 1-4 continuously decreased with increasing temperature under low-temperature conditions (20℃-50℃), indicating that the fluid loss reducing agent did not exhibit significant hydrophobic association in this temperature range. When the temperature increased (>50℃), the viscosity of the fluid loss reducing agent continuously increased with increasing temperature, indicating that the fluid loss reducing agent exhibited significant hydrophobic association in this temperature range, with the molecular chains of the fluid loss reducing agent associating with each other to form a physical network structure, thereby enhancing the binding of free water by the fluid loss reducing agent. In contrast, the viscosity of the linear copolymer fluid loss reducing agent in Comparative Example 1 decreased with increasing temperature, which is not conducive to the fluid loss reducing agent playing a role in thickening and controlling fluid loss under high-temperature conditions.

[0109] Experiment Example 4: Electron Microscopy and Resonance Testing

[0110] High-temperature and high-pressure dehydration experiments were conducted on the cement slurry prepared in Example 2 and Comparative Example 1 (the same cement slurry as in Experiment 1). Specifically, the dehydration experiment refers to a static filtration loss experiment. This experiment was conducted according to API standards and required high-temperature and high-pressure conditions. The filter cake collected after the dehydration experiment was subjected to electron microscopy and full-diameter core NMR spectroscopy. Full-diameter core NMR spectroscopy detects hydrogen in the sample and generates a T2 spectrum based on the hydrogen distribution, thereby calculating information such as the pore size distribution of the sample.

[0111] Test results are as follows Figure 3 (Scale bar 200μm) Figure 4 As shown, the cement filter cake surface with the added water loss reducing agent in Comparative Example 1 is loose, with noticeably large pore sizes, and the overall surface of the filter cake is mainly formed by the compaction of large particles. In contrast, the water loss reducing agent in Comparative Example 2 is mainly composed of two nanomaterials with different particle sizes (hydroxyl carbon nanotubes (HCNTs) and nano-silica (NS), where NS promotes cement hydration; the hydroxyl carbon nanotubes have an outer diameter of 30–80 nm and a length <10 μm; the nano-silica has a size of (30±5) nm). Therefore, after adding cement slurry, the filter cake becomes denser due to the close packing theory, with fewer micron-sized large pores, and the overall surface of the filter cake is composed of small particles. The two test results demonstrate that the water loss reducing agents in these examples can reduce water loss by improving the quality of the filter cake.

[0112] Although the present invention has been described in detail through the preferred embodiments above, it should be understood that the above description should not be considered as a limitation of the present invention. Various modifications and substitutions to the present invention will be apparent to those skilled in the art after reading the above description. Therefore, the scope of protection of the present invention should be defined by the appended claims.

Claims

1. A cementing agent for toughening, weakly retarding setting, and reducing fluid loss, characterized in that, This water loss reducing agent is prepared from the following components in the indicated mass percentages: 20-35% adsorbent monomer, 10-15% thermosensitive monomer, 5-10% heat-resistant rigid monomer, 0.5-1.5% modified nanocomposite material, 0.1-0.5% initiator, and 45-60% water; The modified nanocomposite material is selected from any one or more of the following: silane coupling agent modified carboxyl carbon nanotubes with silica grafted on the surface, hydroxyl carbon nanotubes, and graphene oxide. The adsorbent monomer is selected from any one of the following combinations: sodium 2-acrylamide-2-methylpropanesulfonate and acrylamide, sodium 2-acrylamide-2-methylpropanesulfonate and itaconic acid, and acrylamide and maleic acid. The temperature-sensitive monomer is selected from any one or more of N,N-diethylacrylamide, N-isopropylacrylamide and N,N-dimethylacrylamide; The heat-resistant rigid monomer is selected from any one or more of maleic anhydride, sodium styrene sulfonate, and N-vinylpyrrolidone.

2. The cementing toughening, weakly retarding, and fluid loss reducing agent according to claim 1, characterized in that, The initiator is selected from ammonium persulfate and / or potassium persulfate.

3. The cementing toughening, weakly retarding, and fluid loss reducing agent according to claim 1, characterized in that, The silane coupling agent is selected from KH-570.

4. A method for preparing a cementing toughening, weakly retarding, and fluid loss reducing agent as described in any one of claims 1-3, characterized in that, The method includes: The adsorbent monomer, thermosensitive monomer, temperature-resistant rigid monomer and modified nanocomposite material were placed in water, heated and stirred until the sample was completely dissolved, and the resulting mixed solution was used as the initial reaction solution. The initial reaction solution is heated to 70-80°C in an inert gas atmosphere to obtain an intermediate reaction solution; The initiator is mixed with water to obtain an initiator solution; The initiator solution was uniformly added dropwise to the intermediate reaction solution, stirred and mixed, and reacted at a constant temperature of 70~80℃ for 3~5h to obtain the liquid polymerization product; The liquid polymer product was dialyzed in a dialysis bag, freeze-dried, and ground to obtain a toughening, weakly retarding, and dehydration-reducing agent.

5. The preparation method according to claim 4, characterized in that, The initiator solution is uniformly added dropwise to the intermediate reaction solution within 1-2 hours and stirred at 200 r / min.

6. The preparation method according to claim 4, characterized in that, The preparation method of the modified nanocomposite material includes: Dissolve one or more of carboxyl carbon nanotubes, hydroxyl carbon nanotubes and graphene oxide in an alcohol solvent, add a surfactant, and ultrasonically disperse at 40°C to obtain dispersion one. Add ammonia / ammonium chloride buffer solution dropwise to dispersion solution one, adjust the pH of the mixed solution to 8-10, and continue ultrasonic dispersion at a constant temperature of 40℃ after the buffer solution is added to make the solution uniformly dispersed to obtain dispersion solution two. Tetraethyl orthosilicate was added to the second dispersion and ultrasonically dispersed at a constant temperature of 40°C. Silica in the dispersion was uniformly grafted onto the surface of carbon nanotubes through Si-OC bonds. The reaction solution was washed and vacuum filtered to obtain a pure primary nanocomposite material. The pH of a 90% ethanol solution was adjusted to 5 with hydrochloric acid. The ethanol solution and the silane coupling agent were then stirred at a constant temperature of 65°C to allow the silane coupling agent to be fully hydrolyzed in the ethanol solution. The pure primary nanocomposite material was added to the hydrolysis solution of the silane coupling agent and stirred at 70°C. After the reaction was completed, the reaction solution was dehydrated and dried at 80°C to finally obtain the modified nanocomposite material.

Citation Information

Patent Citations

  • Preparation method and application of nano low-friction temperature-sensitive anti-drag thickening agent

    CN115093515A